Pengembangan Website E-Marketing: Studi Kasus Pada PT. Usaha Gedung Bank Dagang Negara - Honni Honni; Fitri Amelia (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Use of the Internet has become a part of business activities, one of which is marketing via the Internet. Marketing is an activity that determines a company’s success. A web-based marketing can eliminate the existing limitations of conventional marketing such as time constraints and distance. Therefore, through this paper is proposed the development of marketing via the internet, or commonly known as e-marketing, so that the company can obtain maximum benefits as expected. The methodology used in the development of e-marketing website is The Seven Stage Cycle of Internet Marketing. The result achieved is a company’s e-marketing website. Conclusions obtained is that by using a web-based marketing, it is expected to help companies overcome the existing deficiencies, and can provide added value in improving promotions to better introduce the company to the market as well as to achieve profit increase.